2002
DOI: 10.1038/sj.ejhg.5200767
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of combined methylenetetrahydrofolate reductase C677T and A1298C mutated alleles in spontaneously aborted embryos

Abstract: The pathogenesis of spontaneous abortion is complex, presumably involving the interaction of several genetic and environmental factors. The methylenetetrahydrofolate reductase (MTHFR) gene C677T and A1298C polymorphisms are commonly associated with defects in folate dependent homocysteine metabolism and have been implicated as risk factors for recurrent embryo loss in early pregnancy. In the present study we have determined the prevalence of combined MTHFR C677T and A1298C polymorphisms in DNA samples from spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
102
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 40 publications
5
102
0
8
Order By: Relevance
“…We read with great interest the recent article by Zetterberg et al 1 that examined the potential role of methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms in contributing to early spontaneous abortions. Zetterberg et al 1 determined the incidence of C677T and A1298C MTHFR mutations in a study cohort (n=80), which consisted of foetal tissue samples from early spontaneous abortions, and a control group (n=125), which consisted of DNA samples from healthy blood donors that were presumably chosen at random.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…We read with great interest the recent article by Zetterberg et al 1 that examined the potential role of methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms in contributing to early spontaneous abortions. Zetterberg et al 1 determined the incidence of C677T and A1298C MTHFR mutations in a study cohort (n=80), which consisted of foetal tissue samples from early spontaneous abortions, and a control group (n=125), which consisted of DNA samples from healthy blood donors that were presumably chosen at random.…”
mentioning
confidence: 95%
“…They also observed that MTHFR mutations, taking into account single or multiple mutations, were more common in the foetal group than adult controls (OR of 14.2, P=0.001), suggesting to them that MTHFR mutations may play a significant role in determining foetal viability, especially during times of high folate demand. Zetterberg et al 1 only observed MTHFR mutations in trans positions and did not identify any 677TT/1298AC, 677CT/1298CC or C77TT/1298CC genotype combinations in either their study or control groups. They propose that there is complete linkage disequilibrium between the two common MTHFR polymorphisms, C677T and A1298C, as MTHFR mutations in cis positions were not identified in their study.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Moreover, we have until now analysed 4500 individuals of Swedish descent and only detected 677T and 1298C alleles in trans configuration (unpublished data). Most studies in the field have reported no or few cases with 677T and 1298C alleles in the cis configuration.…”
mentioning
confidence: 99%